The Golden Triangle : inside Southeast Asia's drug trade - Chin, Ko-lin (Cornell University Press, 2009)
"The Golden Triangle region that joins Burma, Thailand, and Laos is one of the global centers of opiate and methamphetamine production. Opportunistic Chinese businessmen and leaders of various armed groups are largely responsible for the manufacture of these drugs. The region is defined by the apparently conflicting parallel strands of criminality and efforts at state building, a tension embodied by a group of individuals who are simultaneously local political leaders, drug entrepreneurs, and members of heavily armed militias. This book provides a portrait of a region in constant transition, a place where political development is intimately linked to the vagaries of the global market in illicit drugs." "Ko-lin Chin explains the nature of opium growing, heroin and methamphetamine production, drug sales, and drug use. He also shows how government officials who live in these areas view themselves not as drug kingpins, but as people who are carrying the responsibility for local economic development on their shoulders."--Jacket